Observations and Numerical Modelling of the Sumatra Tsunami of 28 March 2005 - Alisa Medvedeva; Alexander Rabinovich (Journal of Marine Science and Engineering)
On 28 March 2005, a major Mw 8.6 earthquake occurred near Nias and Simeulueislands, in the vicinity of northwestern Sumatra (Indonesia). The earthquake generated a significant tsunami. Although it was not as destructive as the 2004 Sumatra tsunami, the 2005 event was of sufficient strength to be recorded by tide gauges throughout the entire Indian Ocean. We selected 12 records for analysis, most from open-ocean islands but also some from continental stations. The maximum wave heights were measured at Salalah (Oman) (87 cm), Colombo (Sri Lanka), Pointe La Rue (Seychelles) and Rodrigues Island (53–54 cm). The dominant wave periods, estimated from frequency–time (f-t) diagrams, were 60–66 min, 40–48 min, and 20 min, which we assume are associated with the 2005 tsunami source. From the same stations, we calculated the mean ratio of the 2004 to 2005 tsunami heights as 5.11 ± 0.60, with the maximum and minimum heights to the west and south of the source region as 9.0 and 2.49, respectively. We also used these data to estimate the mean energy index, <semantics>E0</semantics> = 65 cm2, for the 2005 tsunami, which was 16 times smaller than for the 2004 event. The USGS seismic solution was used to construct a numerical model of the 2005 tsunami and to simulate the tsunami waveforms for all 12 tide gauge stations. The results of the numerical computations were in general agreement with the observations and enabled us to map the spatial wave field of the event. To estimate the influence of location and orientation of the source area on the propagating tsunami waves, we undertook a set of additional numerical experiments and found that this influence is substantial and that these factors explain some of the differences between the physical properties of the 2004 and 2005 events.